Mental Health Policy and Planning: Continuing the Debates - Pillay, Yogan; Freeman, Melvyn (PINS-Psychology in Society, 2026)
This paper will outline progress in developing a new mental health policy for South Africa. Up to this point there has been no coherent mental health policy, rather mental health interventions have been largely determined by the provisions of the Mental Health Act, 1973, as amended. This Act deals with various aspects of the treatment of mentally ill persons, inter alia, conditions under which people may be detained in psychiatric institutions, State patients, the licensing of institutions for the mentally ill and the establishment of hospital boards. It does not, for example, mandate the State to provide adequate and appropriate mental health care for the country's citizens. Without a holistic policy the provisions of the Act functioned as the de facto mental health policy for the country! This legacy is compounded by racially discriminatory practices and fragmentation that resulted from the influence of apartheid ideology on the provision of mental health care.